Between oceans: stepping-stone dispersal and the Pacific-to-Atlantic expansion of Chinook salmon across Patagonia - Riva-Rossi, Carla; Ciancio, Javier; Gomez-Uchida, Daniel; Pascual, Miguel; Clarke, Rodrigo; Quiroga, Pamela; Di Prinzio, Cecilia; Lázari, Carolina; Garza, John Carlos (Frontiers in Marine Science, 2025)
IntroductionBiological invasions are major drivers of biodiversity loss worldwide, and salmonid introductions are among the most transformative events in the Southern Hemisphere. The rapid, large-scale expansion of Chinook salmon (Oncorhynchus tshawytscha) across South America, driven by high migratory capacity, straying rates, and genetic adaptability, constitutes an unprecedented salmonid invasion. In Patagonia, this spread is accelerating, yet the mechanisms enabling long-distance marine dispersal, successful freshwater colonization, and secondary expansion remain poorly understood. A recently established population in the De las Vueltas River (DLVR), an upper tributary of the Santa Cruz River in Argentine Patagonia, was examined as a key node in the invasion network connecting Pacific-origin populations with new Atlantic Ocean basins.MethodsTwo high-resolution SNP panels (96 and 172 loci) were used to investigate the genetic origins and colonization dynamics of the DLVR population. Tissue samples from 70 fish collected in 2014–2015 were genotyped and compared with North American source lineages to infer ancestral origins, and with Pacific and Atlantic naturalized populations to reconstruct recent invasion pathways. Discriminant analysis of principal components (DAPC), genetic mixture modeling, and Bayesian assignment implemented in the R package rubias were performed. Simulations were used to harmonize SNP data across panels and to improve assignment accuracy.ResultsThe genetic roots of the DLVR population were traced to stocks from the Lower Columbia River fall and spring runs and the Willamette River spring run. Strong genetic affinities were detected with naturalized populations from Chile’s Aysén Region, particularly the Cobarde and Vargas Rivers, while smaller contributions from Santa Cruz River populations were inferred. These findings indicate colonization through long-distance oceanic or trans-Andean dispersal, followed by secondary expansion within the Santa Cruz basin.DiscussionThe role of ocean connectivity, stepping-stone habitats, and leading-edge dispersal in enabling the rapid eastward spread of Chinook salmon is highlighted by these results. The Santa Cruz River basin is identified as a critical invasion hub, concentrating propagules from multiple lineages and promoting multi-step dispersal into new Atlantic Ocean basins. These insights emphasize the need to incorporate riverine connectivity and invasion hubs into management strategies to mitigate the ecological and evolutionary impacts of Chinook salmon in South America.